Pengaruh Penggunaan Perturb & Observe pada MPPT terhadap Daya Keluaran Sel Surya - Dalimunthe, Ernando Rizki; Kurniawan, Freddy; Lasmadi, Lasmadi (Sekolah Tinggi Teknologi Adisutjipto, 2019)
Optimizing the solar cell output power requires a tracker. The tracker which produce a maximum output power is called a maximum power point tracking (MPPT). In this research, each component in MPPT is modeled into Simulink. By using a perturb and observe (P & O) algorithms, this simulation is designed to optimize the solar cell output power. The output of the algorithm is a duty cycle. This parameter is fed into a buck-boost converter to convert the solar cell output voltage to the output voltage. The simulation results show that MPPT can increase the output power up to 37.82% dispite of the sun irradiation, temperature and load changes.